Evaluating Summer Neutral Temperature and Land Surface Temperature Trends Over Three Decades in Tetuan, Morocco Using Thermal Comfort Questionnaires - Ahsissene Safae; Rhziel Fatima Zahrae; Raissouni Naoufal (E3S Web of Conferences)
This study investigates the evolution of summer neutral temperatures and land surface temperature (LST) trends in Tetuan, Morocco, over three decades using data from thermal comfort questionnaires. Integrating subjective assessments with objective temperature data, we identify significant shifts in neutral temperatures influenced by climate change. Analysis of thermal sensation votes from 423 respondents relative to recorded temperatures has allowed for the development of neutral temperature thresholds. These findings contribute to a comprehensive model of urban thermal dynamics, highlighting the impact of temperature variability on urban planning and public health strategies. The unique juxtaposition of subjective thermal perceptions and objective data not only maps the adaptability of urban populations to changing climates but also aids in formulating strategies to enhance thermal comfort in Mediterranean urban settings.